Problems in Accepting Indonesian Candidates for Nurses and Certified Caregivers in Japan: Career Achievement of the Candidates Based on Qualitative Interviews - Saito, Ayami (UI Scholars Hub, 2014)
Under the Japan-Indonesia Economic Partnership Agreement (JIEPA), the Japanese Government allows nurses and caregivers from Indonesia to join a training program in Japan. These nurses and caregivers are obliged to take an examination by the end of the training program, and if they pass the exam, they will get a work permit for a couple of years in Japan. However, there are cases where these nurses and caregivers have passed the examination and received the work permit, yet they opted to go back to Indonesia rather than continued to work in Japan. This paper seeks to explain how and why such case happened. This paper also tries to see how the former participants of JIEPA applied their previous experience in Japan to their current life in Indonesia. By interviewing the nurses and caregivers that once joined JIEPA program, it was discovered that family matters and inappropriate treatment from fellow colleagues at work are the two main reasons why these participants decided to go back to Indonesia after they passed the examination. As for their current life in Indonesia, many of these participants do not really feel the benefit from their previous experience, mostly because the demand for skilled nurses and caregivers is limited in Indonesia. Also, their Japanese language skill may only be useful if they are willing to work in a Japanese company.